Aplikasi Augmented Reality Tentang Pengenalan Tanaman Obat Rumahan Berbasis API - Nasrullah Khomaeni; Muhammad Zakariyah (JSAI (Journal Scientific and Applied Informatics), 2023)
Augmented Reality is a combination of real and virtual object technologies simultaneously. Augmented Reality refers to research with computers that have the aim of realizing a knowledge system that facilitates human work. The problem faced is the lack of public knowledge about medicinal plants and difficulties in studying them. This research aims to develop Augmented Reality applications that can help people recognize and understand the types of home medicinal plants and their benefits using more modern technology. This application uses the Marker Based Tracking method in designing it, with data retrieval through API and testing using Black Box Testing, distance testing, and light intensity testing. Test results with BlackBox Testing is an application that is able to display sound, text, and 3D objects, and can be run on Android smartphones. For distance testing, 3D objects can be read if the distance is between 5-30 cm with an angle of 900. For the results of the Light Intensity Test, if the brightness of the room ranges from 10% - 100%, the marker can be read clearly. This application is expected to provide easy, efficient, and interesting assistance for the community in learning and utilizing home medicinal plants.